12x-(3x-12)=5+8x

Simple and best practice solution for 12x-(3x-12)=5+8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-(3x-12)=5+8x equation:


Simplifying
12x + -1(3x + -12) = 5 + 8x

Reorder the terms:
12x + -1(-12 + 3x) = 5 + 8x
12x + (-12 * -1 + 3x * -1) = 5 + 8x
12x + (12 + -3x) = 5 + 8x

Reorder the terms:
12 + 12x + -3x = 5 + 8x

Combine like terms: 12x + -3x = 9x
12 + 9x = 5 + 8x

Solving
12 + 9x = 5 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
12 + 9x + -8x = 5 + 8x + -8x

Combine like terms: 9x + -8x = 1x
12 + 1x = 5 + 8x + -8x

Combine like terms: 8x + -8x = 0
12 + 1x = 5 + 0
12 + 1x = 5

Add '-12' to each side of the equation.
12 + -12 + 1x = 5 + -12

Combine like terms: 12 + -12 = 0
0 + 1x = 5 + -12
1x = 5 + -12

Combine like terms: 5 + -12 = -7
1x = -7

Divide each side by '1'.
x = -7

Simplifying
x = -7

See similar equations:

| 2x^3+54= | | -3(6n-4)+3n= | | (x-1.4)=36 | | 36(x-1.4)= | | 20m^2+43m+14= | | 11-45=5(x-3)-4 | | 17(5c-1)-14=83c+17 | | -19n+12=-15n-12 | | 42=-7y | | 11=u-7 | | 2.5h=80 | | 11-12b=3 | | 4u+8=5u+3 | | 2.5=80 | | 4x=3x-7 | | 3y-y=4-18 | | 5t^2-8t=3 | | -3=7y | | -3v=-18 | | 5-8x=55-22x | | 6=v+15 | | -9+14=-2u+7u | | -0.625+m=0.333334 | | -6v-6v=-7-18 | | 7v-1=6v-6 | | 4x+33=14x-77 | | 30X-6=4 | | 5x^3-2=x-x^2 | | 4+3=-2w-3w | | x^2+4x+10=3 | | 7(2x-4)=2x+8 | | 5x+3=4x+4 |

Equations solver categories